A new species, Castela juyyaania (Simaroubaceae), and three new records for the semiarid flora of Sinaloa, Mexico - Pío-León, Juan F.; Carrillo-García, Jesús A.; Salomón-Montijo, Bladimir; Márquez-Salazar, Gilberto (Instituto de Ecología, A.C., 2023)
Background and Aims: During biological explorations in the thorn forest near the coast of Sinaloa, specimens of four taxa not previously reported for this state were collected, including the first record of the genus Castela, being also a species new to science. The objective of this work was to describe and illustrate Castela juyyaania, as well as to report three additional new records for the flora of Sinaloa that share habitat with the new species. Methods: Botanical collections in northern Sinaloa during 2022 and 2023 were carried out. For the description of the new species the available literature of the genus Castela was reviewed, and specimens from local herbaria and electronic databases were consulted. An identification key to the species of the section Castela in Mexico, distribution map, a table comparing the most similar species and vulnerability assessment (according to the International Union for Conservation of Nature (IUCN)) were prepared. Photos and updated distribution maps are presented for the new records. Key results: Castela juyyaania is microendemic to the Peninsula El Guachapori in the north of Sinaloa. It grows in thorn forest near the coast, in an area of approximately 25 km2, highly threatened by agricultural expansion. According to the IUCN criteria, it is considered Critically Endangered. It is morphologically similar to the C. erecta complex, but differs in having petiolate leaves, not conspicuously revolute margins, styles present and non-reticulate seeds. The distribution area presents some elements of the Sonoran Desert, including the new records Ebenopsis confinis, Gossypium davidsonii and Malpighia diversifolia. Conclusions: With the new addition, the genus Castela reaches seven species in Mexico with four endemics, consolidating it as its main center of diversity. The new records and the new species provide valuable elements for the conservation of the highly threatened dry forests in Mexico and Sinaloa.